Partycypacyjny potencjał terenowych rad oświatowych w kreowaniu społeczeństwa obywatelskiego - Kosiorek, Małgorzata (Studia Edukacyjne, 2020)
In Poland, since 1989, there have been ongoing processes of decentralization and socialization of state education. One of the fundamental conditions for the democratization of education is the possibility of creating, at various levels of public self-government, advisory, consultative and control authorities in the form of educational councils. Since the 1990s, the legislation has included and described the competences and tasks of educational councils at the level of voivodships, poviats and communes. Unfortunately, the last three decades in educational policy have proved that Polish society cannot create an education policy and build the civil society.